Direct and indirect vector control of a doubly fed induction generator based in a wind energy conversion system - Manale Bouderbala; Badre Bossoufi; Ahmed Lagrioui; Mohammed Taoussi; Hala Alami Aroussi; Yasmine Ihedrane (Institute of Advanced Engineering and Science, 2019)
In the recent years, the development and the exploitation of renewable energy knew a great evolution. Among these energy resources, the wind power represents an important potential for that the wind system has been the subject of several researches. The purpose of this study is to improve the power extracted from wind energy, taking into consideration the variation of wind speed which causes a problem in energy production. For this purpose, we have controlled the powers whether it is active or reactive delivered by the generator. This paper, presents essentially the modeling and control of doubly- fed induction generator (DFIG), which is connected to a variable speed wind turbine. Firstly, the model of the wind power system with the maximum power point tracking (MPPT) strategy is shown. Then, the modeling of doubly- fed induction generator (DFIG) and its power control is presented. Finnaly, to ensure the attitude of these controls the simulations is presented in the Matlab/Simulink environment.